2018
DOI: 10.3389/fendo.2017.00372
|View full text |Cite
|
Sign up to set email alerts
|

Short-Chain Fatty Acids Differentially Affect Intracellular Lipolysis in a Human White Adipocyte Model

Abstract: Background and aimsGut-derived short-chain fatty acids (SCFA), formed by microbial fermentation of dietary fibers, are believed to be involved in the etiology of obesity and diabetes. Previous data from our group showed that colonic infusions of physiologically relevant SCFA mixtures attenuated whole-body lipolysis in overweight men. To further study potential mechanisms involved in the antilipolytic properties of SCFA, we aimed to investigate the in vitro effects of SCFA incubations on intracellular lipolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 36 publications
1
78
0
Order By: Relevance
“…Although it is impossible to speculate as to whether the reduced excretion of VFAs in those animals losing less weight is due to a reduced production and/or increased absorption, a human study identified that faecal acetate concentrations were inversely associated with acetate absorption from the rectum and distal colon [56]. Furthermore, a recent human study confirmed that acetate is primarily responsible for the inhibition of intracellular lipolysis in human multipotent adipose tissue-derived stem cells [57]. Therefore, one possible explanation for the lower weight-loss observed in animals with lower pre-diet faecal acetate concentrations could be that these animals are more metabolically efficient and have a greater production/absorption of VFAs into the circulation, inhibiting lipolysis and providing the host with a source of energy to limit the effects of the negative energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is impossible to speculate as to whether the reduced excretion of VFAs in those animals losing less weight is due to a reduced production and/or increased absorption, a human study identified that faecal acetate concentrations were inversely associated with acetate absorption from the rectum and distal colon [56]. Furthermore, a recent human study confirmed that acetate is primarily responsible for the inhibition of intracellular lipolysis in human multipotent adipose tissue-derived stem cells [57]. Therefore, one possible explanation for the lower weight-loss observed in animals with lower pre-diet faecal acetate concentrations could be that these animals are more metabolically efficient and have a greater production/absorption of VFAs into the circulation, inhibiting lipolysis and providing the host with a source of energy to limit the effects of the negative energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolites and byproducts generated by the microbiota also play an important role as components influencing inflammatory and metabolic processes as well as modulating the intestinal barrier function [125][126][127]. Molecules such as acetate, propionate, and butyrate -short-chain fatty acids (SCFAs) -produced as a result of the fermentation processes performed by the microbiota, can act as signaling and regulatory molecules involved in inflammation and insulin sensitivity [128][129][130][131]. Under non-obese conditions, SCFAs do not accumulate since they are transported through the portal vein, reaching the liver for clearance [132].…”
Section: Gutmentioning
confidence: 99%
“…13 Nevertheless, under the conditions of "leaky" gut permeability caused by severe tissue damages and senescence, SFCA exerts their metabolic regulations on host stem cells through binding to G-protein coupling receptors, subsequently suppressing insulin signalling and causing malfunctions of mitochondrial electron transport chain activity accompanied with the imbalance of NAD+/ NADH ratio and dysregulation of NAD-dependent deacetylase sirtuin-1(SIRT1)/peroxisome proliferator activated receptor gamma coactivator 1 alpha(PGC1α) pathway. 14,15 As a result, more damaged mitochondria results along with an accumulation of ROS and imbalance between glycolysis and OXPHOS, eventually erroneous differentiation and proliferation of stem cells and in turn depletion of stem cell. 16 Evidence in support of this notion comes from old HSCs ex- 19 In line with butyrate, another SFCA propionate also demonstrates the inhibitory effect on the differentiation capacity of human chorion-derived mesenchymal stem cells (sMSCs) 20 .…”
Section: Host Microbiome and Metabolic Changes In Stem Cell Ageingmentioning
confidence: 99%